Canopy plant composition and structure of Cape subtropical dune thicket are predicted by the levels of fire exposure - Strydom, Tiaan; Kraaij, Tineke; Grobler, B. Adriaan; Cowling, Richard M. (PeerJ (San Francisco, CA), 2022)
The subtropical dune thicket (hereafter "dune thicket") of the Cape Floristic Region experiences a wide range of fire exposure throughout the landscape, unlike other dry rainforest formations that rarely experience fire. We sought to determine how fire exposure influences species composition and the architectural composition of dune thicket. We used multivariate analysis and diversity indices based on cover abundance of species to describe the species composition, architectural guild composition and structure of dune thicket sites subject to different levels of fire exposure, namely low (fire return interval of >100 years), moderate (fire return interval of 50-100 years), and high (fire return interval of 10-50 years). The diversity, cover abundance and architectural guild cover abundance of dune thicket canopy species were strongly influenced by the level of fire exposure such that each level was associated with a well-circumscribed vegetation unit. Dune thickets subject to low fire exposure comprises a floristically distinct, low forest characterized by shrubs with one-to-few upright stems (ca. 4-8 m tall) and a relatively small canopy spread (vertical growers). Of the 25 species in this unit, 40% were restricted to it. Dune thickets subject to moderate fire exposure had the highest abundance of lateral spreaders, which are multi-stemmed (ca. 3-6 m tall) species with a large canopy spread and lower stature than vertical growers. None of the 17 species found in this unit was restricted to it. Dune thickets subject to high fire exposure had the highest abundance of hedge-forming shrubs, these being low shrubs (ca. 0.6-1.4 m tall), with numerous shoots arising from an extensive system of below-ground stems. Of the 20 species in this unit, 40% were restricted to it. Multivariate analysis identified three floristic units corresponding to the three fire exposure regimes. Compositional structure, in terms of species and architectural guilds, was most distinctive for dune thickets subject to high and low fire exposure, while the dune thicket subject to moderate fire exposure showed greatest compositional overlap with the other units. Fire exposure profoundly influenced the composition and structure of dune thicket canopy species in the Cape Floristic Region. In the prolonged absence of fire, the thicket is invaded by vertical-growing species that overtop and outcompete the multi-stemmed, laterally-spreading shrubs that dominate this community. Regular exposure to fire selects for traits that enable thicket species to rapidly compete for canopy cover post-fire the prolific production of resprouts from basal buds below- and above-ground. The trade-off is that plant height is constrained, as proportionately more resources are allocated to below-ground biomass.